Pendampingan dan Pengembangan Usaha Mikro Kecil dan Menengah Piscok Mbak Dea melalui Branding Produk di Era Digital - Rinda Citra Septiana; Syahrani Amalia Putri; Boyke Dian Nugroho; Syaiko Rosyidi (Lembaga Pengembangan Kinerja Dosen, 2025)
Abstract. SMEs (Micro, Small, and Medium Enterprises) are a key pillar of Indonesia's economy, playing a significant role in job creation, economic equity, and the growth of the real sector. To help entrepreneurs thrive in facing market challenges, mentoring activities are crucial. One such mentoring activity was conducted for the Piscok Mbak Dea SME, located in Ngotet Village, Rembang District. Throughout her business journey, Mbak Dea encountered several issues, such as a lack of promotion, both online and offline, leading to low brand recognition. Additionally, her business did not have a legal business permit or a business logo as an identity. To address these challenges, a series of mentoring activities were conducted, with the goal of strengthening branding, expanding marketing through social media, and reinforcing the business's legal standing. The strategies implemented included creating a logo, brand, and banner to establish the business identity. To enhance product marketing, training on managing social media accounts was provided, helping Mbak Dea reach a broader audience. Furthermore, assistance was given in obtaining a legitimate business license to ensure the sustainability of the business. As a result of the mentoring activities, the Piscok Mbak Dea business now has a logo, brand, and banner as its identity, a well-organized menu catalog, an active social media presence, and a business license that validates its operations. This mentoring process is expected to serve as a model for developing other SMEs in overcoming market challenges.